Seed longevity of Buchanania siamensis in reclaiming salt-affected areas in Thailand - Yongkriat KU-OR; NISA LEKSUNGNOEN; CHATCHAI NGERNSAENGSARUAY; TUSHAR ANDRIYAS (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ku-or Y, Leksungnoen N, Ngernsaengsaruay C, Andriyas T. 2020. Seed longevity of Buchanania siamensis Miq. in reclaiming salt-affected areas in Thailand. Biodiversitas 21: 743-747. Inland salinity is a grave threat to soil fertility as it causes loss of arable land. Salt-tolerant species, such as Buchanania siamensis Miq., can be used for the reclamation of land affected by salinity. We investigated the appropriate conditions to store the seeds of B. siamensis and the storage duration after which the seeds can still germinate. Storage methods included cooling at 4°C and storing at room temperature (between 25-30°C). Seeds kept at 4°C had low germination (6.75% ± 1.71), with longevity of only up to a week, compared to seeds stored at room temperature, which had germination of 94% ± 4.00 and could be stored for more than 200 days. Seed-longevity test was conducted at 14 levels (the number of storage days). Germination was reduced by 50% after 3.5 months, indicating that the seed could only be stored for the short term. The seeds were classified as having an intermediate behavior in which the germination increased exponentially with increasing seed moisture content. We recommend that seeds be stored at a temperature between 25 and 30°C, with sowing done within 3.5 months to obtain germination at or above 50%.